PENGARUH SIKAP DAN DUKUNGAN KELUARGA PASIEN TUBERKULOSIS PARU TERHADAP KEPATUHAN MINUM OBAT ANTI TUBERKULOSIS DI PUSKESMAS TARUS KABUPATEN KUPANG - yuan christine ratu; Akto Yudowaluyo; Balbina A M Wawo (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2021)
Abstract Tuberculosis is a direct infectious disease caused by mycobacterium tuberculosis bacteria. In 2014, Indonesia was ranked second in the country with the most tuberculosis sufferers after India. This research was a quantitative study with a cross-sectional approach to 62 respondents, with a purposive sampling technique in one puskesmas under the authority of the Health Office of Kupang regency in August 2019. Data collection used three instruments, namely attitude questionnaire, family support and adherence questionnaire of Morisky Medication Adherence Scale ( MMAS). Data were analyzed using nonparametric statistics and multiple linear regression tests.75.8% of respondents had good attitude. 75.8% of respondents had good family support. 75,8% of respondents found ti be well shown. The results of multiple linear regression tests obtained p-value = 0.001 that was under 0.05. Statistical counts were found to be meaningful or there was an impact between attitude variables and family support for medication adherence. Therefore, it is advisable to involve the family in the treatment process. Keywords: attitude, family support, adherence of taking anti-tuberculosis medication